Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru: Systematic Literature Review - Penti Yulyanti (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the influence of school leadership on teacher performance. Such leadership is considered essential for creating a supportive work climate, boosting motivation, and fostering professionalism in carrying out educational responsibilities. The research adopts a qualitative approach using the Systematic Literature Review (SLR) method, reviewing 15 selected articles. The analysis reveals that styles such as transformational, democratic, and instructional positively contribute to improving teachers’ effectiveness in lesson planning, classroom instruction, and evaluation. These findings highlight the importance of enhancing principals’ leadership capacity to build a productive and quality-oriented educational environment.